2010
DOI: 10.4137/idrt.s6033
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic Abnormalities in Treatment-naïve HIV Patients

Abstract: Objectives: Hematologic abnormalities, indicated by a deranged full blood count, are common manifestations and important prognostic tools for human immunodeficiency virus (HIV) infection and AIDS. This study aimed to determine the prevalence of cytopenia and its relationship to the degree of immunosupression in HIV treatment-naïve patients. Methods: This was a cross-sectional study of treatment-naïve HIV-infected clients who enrolled at the HIV clinic of Lagos State University Teaching Hospital (LASUTH) betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
47
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(82 citation statements)
references
References 15 publications
25
47
10
Order By: Relevance
“…As encountered by Akinsegun Akinbami et al, 5 in the present study, we found 25 out of 120 cases (21%) having leucopenia ( Table 1). Among the 44 cases which were not on ART, mild to moderate leucopenia was found in 19% (N=6/44) of cases.…”
Section: Leucopenia In Hivsupporting
confidence: 75%
See 2 more Smart Citations
“…As encountered by Akinsegun Akinbami et al, 5 in the present study, we found 25 out of 120 cases (21%) having leucopenia ( Table 1). Among the 44 cases which were not on ART, mild to moderate leucopenia was found in 19% (N=6/44) of cases.…”
Section: Leucopenia In Hivsupporting
confidence: 75%
“…This was done to sort out the HIV cases by disease severity. A similar CD4 intervals were used by Akinbamiet al, 5 in his study "Hematological abnormalities in treating naïve HIV patients" to bring out the relationship between varying degrees of CD4 count and cytopenias.…”
Section: Methods Of Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…The impact on haematology services is singularly notable because of the numerous haematological complications of HIV infection, which occur secondary to effects of the virus itself, as a result of associated opportunistic infections/malignancies, or as adverse drug effects. [1] Several studies have reported the prevalence of haematological complications in HIV-seropositive patients, [2][3][4][5][6][7] with variables such as disease stage and exposure to antiretroviral therapy (ART) being important determinants. [8] However, there is a paucity of published SA data in this regard, despite the fact that the burden of HIV infection in SA is among the highest in the world.…”
Section: Researchmentioning
confidence: 99%
“…[9] Documenting the SA experience in this respect is important, as the prevalence of some cytopenias has been shown to vary geographically, with anaemia being more prevalent among treatment-naive patients with AIDS from Africa than among those from Asia or the Americas. [5] Furthermore, geographical differences have been reported within Africa, with the prevalence of anaemia in patients with immunological AIDS (iAIDS) being 32.2%, 49.3% and 58.0% in Rwanda, [6] Uganda [7] and Nigeria, [4] respectively. The prevalence of cytopenias in SA patients is therefore of interest.…”
Section: Researchmentioning
confidence: 99%